EFFECT OF STRESS AND PROFESSIONAL BURNING ON MORAL VALUES IN PHYSIOTHERAPY PROFESSION - Jovanović, Stevan (PONS - medicinski časopis, 2017)
OVERVIEW The principles of rehabilitation are based on holistic medicine considering physical, mental and social aspects of the patient. In recent decades, we have witnessed intensive changes through the entire medical profession, that are caused by the tremendous advances in science and technology. The communication process between therapist - patient, and between all members of the medical team requires sensitivity to the problems of the patient. It includs honesty, empathy, active listening, patience and also represent the guidelines for successful communication that are necessary for the creation of mutual trust. The state of disease and disability changes every man and reinforces a sense of personal weakness. The patient that is faced with the weakness, needs words of comfort and accepts the help of another person. For a better understanding of the patient’s suffering and fears in a therapeutic procedure, it is necessary to activate the empathic power primarily achieve high quality communication with the patient. Communication in medicine is considered as a core skill. Knowledge and good communication skills are a prerequisite for quality work for many professions, especially medicine. According to numerous studies, physiotherapists are primary candidates for combustion at work because of close contact with customers in the work of physiotherapy. Physical therapists, who experience burning, feel helpless in their ability to help others, and can not create a quality relationship with their patients. The resulting changes are loss of empathy and ethical values ​​that were most important features of health services for many decades. Key words: physiotherapy, physiotherapist, moral values, stress, burnout syndrome